1991
DOI: 10.1203/00006450-199102000-00007
|View full text |Cite
|
Sign up to set email alerts
|

The 22-kD Peroxisomal Integral Membrane Protein in Zellweger Syndrome—Presence, Abundance, and Association with a Peroxisomal Thiolase Precursor Protein

Abstract: ABSTRACT. The primary genetic defect of Zellweger syndrome may be related to defective synthesis or impaired import of peroxisomal proteins. We analyzed the presence and measured the abundance of the 22-kD peroxisomal integral membrane protein (PMP) in patients with Zellweger syndrome. We determined the intracellular localization of the 22-kD PMP and compared it with the localization of a peroxisomal 44-kD thiolase precursor protein.The 22-kD P M P was quantified by immunoblot analyses in liver tissue (n = 7 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…7). The shift to lower density fractions of peroxisomal membranes (ghosts) has been reported before (Santos et al, 1988;Gärtner et al, 1991;van Roermund et al, 1991;Motley et al, 1994;Hettema et al, 2000). Furthermore, differential centrifugation experiments (Fig.…”
Section: Colocalization Of Pmps In Pex1 and Pex6 Cellssupporting
confidence: 80%
“…7). The shift to lower density fractions of peroxisomal membranes (ghosts) has been reported before (Santos et al, 1988;Gärtner et al, 1991;van Roermund et al, 1991;Motley et al, 1994;Hettema et al, 2000). Furthermore, differential centrifugation experiments (Fig.…”
Section: Colocalization Of Pmps In Pex1 and Pex6 Cellssupporting
confidence: 80%
“…the �-oxidation enzymes) appear to be rapidly degraded in the cytosol. Interestingly, seemingly empty vesicular structures that contain some but not all of the peroxisomal integral membrane proteins and that may also contain the unprocessed thiolase precursor are found in the tissues of some Zellweger patients (19,82). The presence of these "peroxisomal ghosts" sug gests that more than one import route may exist and that not necessarily all routes are defective in peroxisome deficiency disorders.…”
Section: Disorders Of Peroxisomal Lipid Metabolismmentioning
confidence: 98%
“…Several investigations have indicated that peroxisomal ghosts fractionate at a lower density than peroxisomes from control cells (Santos et al, 1988;Gartner et al, 1991;Van Roermund et al, 1991). Subcellular fractionation was performed to investigate whether the prethiolase-containing particles in group IV cells also fractionate at a lower density than peroxisomes from control cells.…”
Section: Group I V Ghosts Fractionate At Low Densitymentioning
confidence: 99%